The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.11613/bm.2018.030703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of annexin A8 antibodies in serum of patients with antiphospholipid syndrome

Abstract: IntroductionAntibodies specific for annexin A8 (AnxA8) have not been investigated in patients suffering from antiphospholipid syndrome (APS) yet. The aim of this study was to compare the presence of AnxA8 antibodies in serum of APS patients with that of age-matched healthy controls and to investigate whether AnxA8 antibodies are potential biomarkers for APS.Materials and methodsWe enrolled 22 APS patients and 22 healthy controls in this case-control study. We used sodium dodecyl sulfate polyacrylamide gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Although the major cellular activities of annexin proteins are internal to cells, several annexins have been observed externally in free form and complexed with phospholipid entities, but whether this external presence is responsible for production of anti-annexin autoantibodies in patients remains unclear. Nevertheless, production of anti-annexin autoantibodies have been proposed to enhance the vulnerability for inflammation and autoimmune disorders by interfering with annexins’ ability to regulate apoptosis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In this sense, it is interesting to note that both NOD/Shi and C57BL/6.NOD- Aec1Aec2 mice have increased levels of cellular apoptosis in the salivary and lacrimal glands prior to onset of clinical SS pathology [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the major cellular activities of annexin proteins are internal to cells, several annexins have been observed externally in free form and complexed with phospholipid entities, but whether this external presence is responsible for production of anti-annexin autoantibodies in patients remains unclear. Nevertheless, production of anti-annexin autoantibodies have been proposed to enhance the vulnerability for inflammation and autoimmune disorders by interfering with annexins’ ability to regulate apoptosis [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In this sense, it is interesting to note that both NOD/Shi and C57BL/6.NOD- Aec1Aec2 mice have increased levels of cellular apoptosis in the salivary and lacrimal glands prior to onset of clinical SS pathology [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported associations between annexins and autoimmune/auto-inflammatory pathologies [ 25 , 26 , 29 , 31 , 32 , 33 , 34 , 35 , 36 ], including the development of anti-annexin autoantibodies [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ], but especially toward Anxa1, Anxa2, Anxa5, Anxa7, and Anxa11. Both over- and under-expressions of annexins are found in development and organ systems as well as pathological conditions ranging from cancers to auto-immune diseases, especially Rheumatoid arthritis (RA), Systemic lupus erythematosus (SLE), and Sjögren’s syndrome (SS).…”
Section: Introductionmentioning
confidence: 99%